2020
DOI: 10.3390/coatings10040423
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Ellipsometric Study of the Optical Properties of LTL-Doped Thin Film Sensors for Copper(II) Ion Detection

Abstract: Optical sensors fabricated in zeolite nanoparticle composite films rely on changes in their optical properties (refractive index, n, and thickness, d) to produce a measurable response in the presence of a target analyte. Here, ellipsometry is used to characterize the changes in optical properties of Linde Type L (LTL) zeolite thin films in the presence of Cu2+ ions in solution, with a view to improving the design of optical sensors that involve the change of n and/or d due to the adsorption of Cu2+ ions. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…[ 88,141 ] Apart from these optical methods, ellipsometry can also be used for measuring thickness of the wide range of thin films. [ 142–146 ] Using ellipsometry variation in the PEM, thickness can be analyzed for studying salt induced molecular exchange or changes with respect to polymer concentration, pH, temperature, etc. [ 113,147–149 ] But, ellipsometry require specialized substrates and complex modelling for data interpretation.…”
Section: Techniques To Probe Transportmentioning
confidence: 99%
“…[ 88,141 ] Apart from these optical methods, ellipsometry can also be used for measuring thickness of the wide range of thin films. [ 142–146 ] Using ellipsometry variation in the PEM, thickness can be analyzed for studying salt induced molecular exchange or changes with respect to polymer concentration, pH, temperature, etc. [ 113,147–149 ] But, ellipsometry require specialized substrates and complex modelling for data interpretation.…”
Section: Techniques To Probe Transportmentioning
confidence: 99%
“…The effects of the annealing temperature on the structural properties, surface roughness, electrical properties, and optical transmittance of the thin films are then systematically explored. Cody et al [6] demonstrated a possibility of optical sensing of copper ions in water using Linde Type L (LTL) zeolite thin films. Both single wavelength and spectroscopic ellipsometry were used for characterization of the changes in optical constants and thickness of films in the presence of heavy metal ions.…”
Section: Brief Overview Of the Contributions To This Special Issuementioning
confidence: 99%
“…Among all these techniques, adsorption is one of the most favorable techniques owing to its fast kinetic response even with a very low detection limit, in addition to its simple operating procedure [22]. In this category, adsorbents in the form of resins, goethite, activated carbons, zeolite nanoparticles and holographic-based sensors have been attempted in the past, but with limited success [23][24][25]. In addition to this, liquid-based colorimetric and fluorescent chemosensors have been reported with numerous probe molecules that are mostly soluble in organic solvent, thus making the sensing process more complicated and less sensitive [26].…”
Section: Introductionmentioning
confidence: 99%